Toward Agricultural Intersectionality? Farm Intergenerational Transfer at the Fringe. A Comparative Analysis of the Urban-Influenced Ontario's Greenbelt, Canada and Toulouse InterSCoT, France - Akimowicz, Mikaël; Landman, Karen; Képhaliacos, Charilaos; Cummings, Harry (Frontiers in Sustainable Food Systems, 2022)
Periurban agriculture can foster the resilience of metropolitan areas through the provision of local food and other multifunctional agricultural amenities and externalities. However, in periurban areas, farming is characterized by strong “social” uncertainties, which slow down the intergenerational transfer of farm operations. In this article, we tackle the beliefs that underlie farmers’ decision-making to identify the planning opportunities for supporting farm intergenerational transfers. The design of an institutionalist conceptual framework based on Keynesian uncertainties and Commonsian Futurity aims to analyze farmers’ beliefs associated with the critical step of farm intergenerational transfer. 41 farmers involved in animal, cash-crop, and horticulture farming in the urban-influenced Ontarios’ Greenbelt, Canada and Toulouse InterSCoT, France were interviewed and designed the mental model of their investment decision-making. The results highlight the existence of a money-land-market nexus, which slows down farm structural change, and results in access inequalities and an agricultural intersectionality. The results also highlight the positive role of the institutional context when farmers’ beliefs and the beliefs shaping their institutional environment, including their family, their professional community, and the surrounding stakeholders such as agricultural organizations, public agencies, and residents of the area, are well aligned and result in a shared vision of the future.